Prevention of HIV-1 TAT Protein-Induced Peripheral Neuropathy and Mitochondrial Disruption by the Antimuscarinic Pirenzepine - Han, May Madi; Frizzi, Katie E.; Ellis, Ronald J.; Calcutt, Nigel A.; Fields, Jerel Adam (Frontiers in Neurology, 2021)
HIV-associated distal sensory polyneuropathy (HIV-DSP) affects about one third of people with HIV and is characterized by distal degeneration of axons. The pathogenesis of HIV-DSP is not known and there is currently no FDA-approved treatment. HIV trans-activator of transcription (TAT) may play a role in the pathogenesis of HIV-DSP as it is associated with mitochondrial dysfunction and neurotoxicity in the brain. Pirenzepine (PZ), a selective muscarinic subtype-1 receptor (M1R) antagonist, has been shown to promote neurite outgrowth by enhancing mitochondrial function in sensory neurons and prevent and/or reverse indices of peripheral neuropathy across multiple disease models. In this study, we measured indices of peripheral neuropathy in the doxycycline-inducible HIV-TAT (iTAT) transgenic mouse model and investigated the therapeutic efficacy of PZ against HIV-DSP. Doxycycline itself was responsible for tactile allodynia and paw thermal hypoalgesia in normal mice. Doxycycline-induced TAT expression altered nerve expression of mitochondrial proteins associated with oxidative phosphorylation and fission (DNM1L) and caused both motor nerve conduction velocity slowing and loss of corneal nerves. Daily injection of PZ (10mg/kg s.c.) prevented all of these disorders. These studies demonstrate that TAT expression disrupts mitochondria and induces multiple indices of peripheral neuropathy. M1R antagonism may be a viable treatment against HIV-DSP.